Children's own perspectives demonstrate the need to improve paediatric perioperative care - Gunilla Lööf; Nina Andersson‐Papadogiannakis; Charlotte Silén (Wiley, 2019)
Abstract Aim To explore children's perspectives when facing anaesthesia and surgery. Design Interpretative qualitative design. Methods Children undergoing outpatient surgery were interviewed in three different phases, before and after anaesthesia and surgery (phase 1 and 2) and 1 month after the hospitalization (phase 3). Twenty‐two children (4-15 years) were interviewed in phase 1 and 2 and six children (5-13 years) in phase 3. Data were analysed using manifest and latent qualitative content analysis. Results Two contrasting themes were identified: Fearful in association with anaesthesia and surgery and Confident in association with anaesthesia and surgery. Comprehension of the perioperative procedures, continuous information and interaction with the healthcare providers were decisive factors for children's expressions of confidence or fearfulness. Events considered as major from a healthcare perspective may be of no importance to the child, while events considered as less important by healthcare providers may be significant to the child. Understanding children's perspectives and awareness of their need to process the information provided are significant factors for establishment of trust and confidence in a highly technological perioperative environment.